Perceiving the Enemy Differently: A Psycho-cultural Analysis of Pakistan–India Conflict. (August 2019) - Kadir, Jawad
Abstract: By using an interdisciplinary approach, this article seeks to examine Pakistan–India partition and their on-going rivalry which is a permanent threat to the South Asian regional security. This article analyses the Pakistan–India conflict through a fresh psycho-cultural framework to explain both states' endless competitive urge to outpace each other. I will describe the attributes of the indigenous 'culture of conflict' in both countries and use them as an 'analogy'. This article develops a conflict theory to explain the rationale behind such an emotion-laden rivalry between the two nations. The conflict theory presented in this article (which can be termed as Sharike-Bazi [Culture of Conflict]) explains that peoples' conflict behaviours in Pakistan and India are rooted in their earliest socialisation within primary kinship institutions. In Pakistan and India, the indigenous 'culture of conflict' emanates from the segmentation of the most pervasive and influential institutions, the kinship institutions. The moralities of conflict behaviour learned within these institutions are extrapolated to every other institution in the outside world. Therefore, psychologically, the indigenous 'culture of conflict' creates certain moral views affecting the conflict behaviour of people as well as policymakers. It provides them with cultural moralities to pursue this zero-sum interstate conflict.